Hubungan Kepadatan Hunian dengan Kejadian Demam Berdarah Dengue di Semarang - Agustina Ratri Maharani; Nur Endah Wahyuningsih; Retno Murwani (Jurnal Kesehatan Masyarakat (Undip), 2017)
Dengue  fever is a transmittable disease which caused by Dengue  virus and transmitted by Aedes aegyptimosquito. There are many factors that influence Dengue  fever such as host factor, environment, and disease agents.DHF is one of the major public health problems in Indonesia, one of which is in Semarang and its surroundings. Incidence Rate (IR) DHF of Semarang District from 2006 to 2016 is always much higher than IR DHF Central Java and IR DHF NationalThe purpose of this research was to analyze the correlation of dwelling density with incidence of Dengue  fever in Semarang. This was a quantitative research with case control study. The samples was 38 cases and 38 controls. Research instrument that was used in this research were questionnaire and food recall form. Data was analyzed using univariate and bivariate with chi square trial with significance level of 95%. The results showed that there was no correlation of dwelling density with incidence of Dengue  fever with p value =0.175(OR 2,634).